Functional anatomy, osteogenesis and bone microstructure of the appendicular system of African mole-rats (Rodentia: Ctenohystrica: Bathyergidae) - Montoya-Sanhueza, Germán Andrés (Department of Biological Sciences, 2021)
In comparison to their ecophysiological and behavioral aspects, the skeletal system of African mole-rats (Bathyergidae) has been relatively understudied. Only a few studies have assessed their skeletal system, but these have mostly focused on their cranial and dental systems, with little attention on their postcranial skeleton. This PhD thesis provides a considerable amount of information about the functional anatomy, morphological diversity and postnatal bone morphogenesis of the appendicular system of these subterranean mammals. African mole-rats are small mammals highly adapted to the hypogeous niche that feed on underground roots and tubers. They forage, mate, breed and to some extent even disperse underground. For this, they build extensive burrow systems primarily with their chisel-like teeth, but also using their forelimbs for scratch-digging. One of the most exceptional features of bathyergids is their wide spectrum of social organization, which is unique among mammals and ranges from solitary, social and eusocial. Here, the eusocial naked mole-rat, Heterocephalus glaber, has been the most studied species. The physiology of African mole-rats is also exceptional among rodents and other mammals, showing low metabolic rates and body temperatures, as well as slow somatic growth rates. They also show enhanced fitness and prolonged longevity, features that have been associated to a life protected from both climatic extremes and predation, as well as to intergenerational transfer of information, communal care of young and shared foraging endeavors in social species. For these reasons, bathyergids represent a unique animal model to explore their skeletal adaptations to fossoriality and life underground. The aim of this research was to assess the patterns of bone growth and development to understand how adults attain their final phenotype. A comprehensive sample (N = 506) of all six bathyergid genera including seven species and comprising individuals of both sexes and of different ontogenetic stages was studied. Stylopodial (humerus and femur) and zeugopodial (ulna and tibia-fibula) bones (n = 1133) were analyzed using multiple quantitative analyses of variance (ANOVA, MANOVA), ordination (PCA, DA) and regression (RMA, OLS, equality of slopes), as well as bone labeling techniques and detailed qualitative descriptions of their midshaft bone histology. Chapter 3 shows that the specialized phenotype of the only scratch-digger bathyergid Bathyergus suillus underwent considerable morphological changes during ontogeny, e.g. juveniles showed externally more robust bones with thin cortical walls, whereas adults presented slender bones with significantly thicker cross-sections. Such changes are probably related to the increased digging demands and agonistic behaviors of the developing young. However, other aspects of their anatomy expressed perinatally, such as greater external epicondylar robustness, well-developed olecranon, teres major and deltoid processes, suggest a major role of genetic factors in their development. This chapter applied for first time the conceptualization of developmental modules to long bones, and showed that the periosteal module had higher variability and tended to grow faster than the endochondral module. Chapter 4 analyzed the morphological diversity within Bathyergidae using comparative anatomy and morpho-functional indices and showed that most species shared a highly specialized fossorial morphology and that only the naked mole-rats were morphologically divergent (having a simplified phenotype), resembling the condition of non-fossorial closest relatives of the Bathyergidae. Nevertheless, the novel inclusion of three ecomorphological categories (solitary scratch-diggers, solitary chisel-tooth diggers and social chisel-tooth diggers) in this study, showed significant differences among the groups. In general, social species appeared to have a phenotype more specialized to increase digging ability and locomotor performance, whereas solitary species showed a relatively less specialized fossorial phenotype, and a diminished locomotor ability. This may contribute to foraging strategies in social species which are known to have more complex and relatively longer burrow systems as compared to solitary species. Chapter 5 assesses the ossification patterns of the endochondral and periosteal modules, and shows that in general most bathyergids have relatively similar endochondral growth rates, irrespective of social behavior or digging strategy, although the periosteal module showed relatively higher growth rates and a higher degree of variation as compared to the endochondral module, thus appearing to be considerably less dependent on body size and genetic factors. Naked mole-rats showed the lowest growth rates among bathyergids. Considering the basal phylogenetic position of H. glaber within the family, a neotenic condition is suggested for this species, and suggests accelerated bone growth rates for the evolution of the other bathyergids. Chapter 6 provides a comprehensive description of the pattern of bone modelling in bathyergids and includes an assessment of their bone dynamics using fluorochrome labeling. All bathyergids analyzed showed increased cortical bone thickening during ontogeny, as well as low rates of endosteal bone resorption. Also, all species showed high histodiversity, limited remodeling (i.e. development of secondary osteons) and they do not ever develop Haversian bone tissues. This thesis concludes that the combination of social strategy and type of excavation had an impact on the evolution of the bathyergid appendicular system. On one hand, it was evidenced that the development of fore- and hindlimbs are not constrained by intrinsic factors (as suggested for other mammals), and that the limbs develop at similar growth rates, resulting in relatively symmetrical limb proportions. This is suggested to improve locomotion within burrows and represents an adaptation to the subterranean lifestyle, which is also observed in other fossorial mammals. This thesis further discusses how environmental factors and specific behaviors and locomotor modes, may represent strong selective pressures on limb adaptation and evolution. Similarly, a proximo-distal pattern of variation was observed, where zeugopodial elements were more variable than stylopodial elements, probably because they are in direct interaction with the substrate, so they can evolve morphological adaptations for particular habitats and locomotor behaviors. Importantly, these adaptations are most likely mediated by heterochronic modifications of their ossification modules, especially intramembranous ossification, which is known to be more responsive to environmental factors, whilst the endochondral modules would be more conservative, perhaps because a stronger genetic regulation in postnatal life. Further research on long bone modules is necessary to understand the specificity of such changes. Despite the comparatively simplified phenotype of H. glaber, they showed a larger morphospace as compared to other bathyergids, indicating a wider intraspecific variability. This agrees with previous observations suggesting skeletal plasticity for this species. It is suggested that living in large colonies results in diminished selective pressures for limb specialization but has an impact on increasing trait variability within members of the colony. This study showed that the integration of multiscale techniques and multivariate analysis of combined skeletal phenotypes (i.e. forelimb + hindlimb) offer a better understanding of adaptations to the hypogeous environment. The findings of this study also highlight the importance of considering developmental modularity of long bones for assessment of bone adaptations, particularly for understanding the differential effects of intrinsic and extrinsic factors regulating endochondral and intramembranous ossification.